Estrogen Activity of OTC Topical Medications Containing Parabens Depends on Paraben Type and Concentration - Allen, Brianna (J Endocr Soc, 2021)
Methylparaben, ethylparaben, and propylparaben are widely used as preservatives in food, cosmetics, and pharmaceutical products. Parabens are also known to bind the estrogen receptor and induce weak estrogen activity in laboratory bioassays. Many OTC topical medications contain one or more parabens as preservative ingredients. In this study, we surveyed the estrogen activity of extracts from OTC topical medications and tested the hypothesis that a combined threshold concentration of particular parabens is required to induce estrogen activity in human breast cancer cell bioassays. Ethanol extracts (1 gm:1 ml) were prepared from OTC topical medications containing parabens (including: Olay Quench Lotion, CeraVe Daily Moisturizing Lotion and Cortizon-10 Lotion). The estrogen agonist and antagonist activity of each extract was determined using the T47dkbluc estrogen reporter gene and the MCF-7 E3 estrogen responsive proliferation assays. The extracts from Olay Quench Lotion and CeraVe Daily Moisturizing Lotion induced estrogen agonist activity in the MCF-7 proliferation assay. The extract from the Cortizon-10 Lotion did not induce significant estrogen activity. The product ingredients of each OTC topical medications tested listed ethyl and propyl parabens while the Olay Quench Lotion also contained the least estrogenic paraben methylparaben. We propose that the estrogenic potential of OTC topical medications can be estimated with LC-MS analysis determination of paraben content and concentration. This study illustrates that measurable estrogen activity from OTC topical medications requires the presence of estrogenic parabens (ethyl and propyl) at total concentrations that exceed a threshold. Thus, estrogen activity depends on the type and concentration of paraben present in the OTC topical products. While the capacity for these OTC topical medications to induce estrogen activity in individuals using the products is unclear, consumers may benefit from more information about the paraben type and concentration present.